Biological flora of Central Europe – Lupinus polyphyllus Lindley - Eckstein R. Lutz; Welk Erik; Klinger Yves P.; Lennartsson Tommy; Wissman Jörgen; Ludewig Kristen; Hansen Wiebke; Ramula Satu (Elsevier GmbH, 2025)
The invasive herb Lupinus polyphyllus has been focus of a number of fact sheets worldwide but a comprehensive summary of the species’ taxonomy and morphology, distribution, habitat requirements, and biology has been lacking. This paper gives a thorough account of the species’ systematic position and taxonomy, highlighting the difficulties to delimit taxa, which is related to interbreeding among members of this genus. However, L. polyphyllus var. polyphyllus is apparently the taxon that has naturalized and is regionally invasive in temperate-humid climates worldwide. We also present an updated distribution map of L. polyphyllus in the native and invaded ranges, which highlights seven regions in the world where the species has been established. We show that the climatic niche of L. polyphyllus in the invaded range shifts towards higher summer precipitation and lower isothermality, probably because the invaded range includes subcontinental regions of eastern Europe and western Siberia. The habitats of L. polyphyllus range from rather dry to wet, have moderately acidic to strongly acidic soils, and the species’ indicator values across Europe suggest that it occurs along a gradient from very nutrient poor sites to intermediate to rich sites from northern to southern Europe. The species shows high resistance to both drought and frost. In Central Europe, the species has a stronghold in alpic mountain hay meadows, abandoned meadows and pastures, low and medium altitude hay meadows, anthropogenic herb stands and temperate thickets and scrubs. In northern Europe, the species occurs in anthropogenic herb stands along roads and railroads as well as in abandoned pastures and fields. We also found some doubtful information about L. polyphyllus in the literature. This refers to its description as “rhizomatous perennial” although it lacks rhizomes; an apparently very high longevity of its seeds, which may only be true under artificial conditions in an ex situ seed repository; and a very deep rooting depth, which may not represent the average rooting depth but rather an extreme value. Knowledge about the interrelationships between the species’ future population dynamics and spread and ongoing climate warming is lacking. Finally, our review points out that there is currently no evidence-based strategy for a cost-efficient management of L. polyphyllus although it is among the most problematic non-native plant species in Europe due to its environmental and socio-economic impacts.